When Heritage Meets Creativity: A Tale of Two Urban Development Strategies in Kampong Glam, Singapore. (3rd September 2019) - Kumar, Vinay
Abstract: In recent years, cities around the world have increasingly relied on culture‐based development strategies for the revitalization of urban areas, such as urban heritage and the development of a creative economy. Typically, either one of these practices is put in place; however, in Kampong Glam, Singapore, both heritage development and creative economy strategies have been adopted by the national government and local organizations. This paper studies the coincidence of the two main culture‐based urban development strategies and its implications in the same physical urban place. Drawing on geospatial mapping techniques and archival data, we aim to illustrate how the two cultural urban redevelopment strategies manifest and interact in urban space. We find that stakeholders draw on each strategy to counteract the excesses of the other, given their different aims and audiences, so as to regulate the interaction between the two and achieve balance among competing interests in the neighborhood.